Wireless Elevator Call System Design With PSoC - Tasci, Burak; Erol, Yavuz (Ieee, 2019)
In this study, a remote elevator call system application was designed and adapted to elevator systems with PSoC (Programmable System on Chip) technology, which has an important place in embedded systems and is widely used today. A 434 MHz UHF FSK UTX-C17U transmitter module and a UHF FSK UFR-C12 receiver module were used in the radio frequency communication system. The serial information package required for the communication of RF modules is provided with a programmable system on the CY8C4245AXI-483 chip of Cypress company. The designed device enables the elevator to reach the floor by using the call button when leaving the house or office, thus minimizing the waiting time of the elevator. This design can be applied to buildings with old elevators without modification thanks to the wireless operation of RF receiver and transmitter modules.
3rd International Conference on Applied Automation and Industrial Diagnostics (ICAAID) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: PSoC; embedded system; RF; elevator